KatE from the bacterial plant pathogen Ralstonia solanacearum is a monofunctional catalase controlled by HrpG that plays a major role in bacterial survival to hydrogen peroxide - Tondo, María Laura (2020)
Fil: Tondo, María Laura. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Área Biología Molecular; Argentina